(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background and Objectives: Computer Vision Syndrome (CVS) refers to the constellation of ocular and musculoskeletal symptoms that develop from prolonged digital screen exposure. To assess CVS awareness, characterise digital device usage patterns, determine the prevalence of CVS-related symptoms, and evaluate associations between screen time, demographic variables, and probable CVS. Methods: A quantitative, cross-sectional, questionnaire-based study was conducted among students and healthcare workers. A sample of 385 participants was determined using standard formula (Z = 1.96, p = 0.5, d = 0.05). Awareness, screen time, device usage, and seven CVS-related symptoms were assessed. Probable CVS was defined as at least one eye-related symptom combined with reported symptom aggravation on prolonged screen use. Descriptive statistics, chi-square tests, and binary logistic regression were applied; statistical significance was set at p < 0.05. Results: A total of 385 participants (mean age 24.8 ± 7.7 years; 50.6% male) were analyzed, comprising predominantly students and healthcare workers. CVS awareness was low at 17.9%. Most participants (68.9%) reported at least four hours of daily screen time. Eye strain (60.3%), headache and blurred vision (both 50.4%) were common. Probable CVS was identified in 58.4% of participants. Higher screen time was significantly associated with symptoms. Male sex (adjusted OR ≈ 1.6, p ≈ 0.045) and healthcare worker occupation (adjusted OR ≈ 3.6 vs. students, p ≈ 0.001) were independently associated with probable CVS. Interpretation and Conclusion: CVS awareness is critically low despite a substantial symptom burden.